THE POLITICS OF PANDEMICS Evolving Regime-opposition Dynamics in the MENA Region - Mezran, Karim; Perteghella, Annalisa (2021)
The Covid-19 pandemic could not have come at a worse time, as many countries in the MENA region remain engulfed in vicious internal conflicts or must cope with structural socio-economic distress and popular dissent. In many respects, such a context and many of its problems resemble those that formed the backdrop for the Arab Spring in 2011. Exactly like what happens with humans, who are hit the hardest when presenting pre-existing conditions, MENA states have been impacted because of their own pre-existing conditions. In this sense, the Covid-19 pandemic has laid bare all the vulnerabilities and deficiencies of these states' structures, and has aggravated pre-existing political, social, and economic shortcomings. How has the pandemic impacted state structures? What is its effect on organized protests and spontaneous popular movements? What are the possible long-term consequences?